ANALISIS KEBUTUHAN PELATIHAN PADA DIVISI CUSTOMER SERVICE & KEY ACCOUNT PT XYZ JAKARTA - Satibi, Muhammad; Sembiring, Indra Refipal; Matoati, Rindang (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
The decline in customer satisfaction scores in the Customer Service Key Account (CS KA) Division of PT XYZ Jakarta indicates the need to improve knowledge, skills, and work behavior through a training program. This training is intended to address the gap between the competencies possessed by employees and the competency requirements for the positions within the division. The purpose of this research is to identify the components of competence, analyze the gap between job competency requirements and personal work competence, and prioritize as well as recommend appropriate training needs for employees of the CS KA Division. The sampling method used is saturated sampling, with a total sample of 19 people. The research methodology applies training need assessment tools (TNA-T) with a KKJ-KKP gap analysis. Data processing is carried out using Microsoft Excel. After analyzing the data, the results show that all positions in the CS KA division, except for the CS Manager, require training. Four competency indicators are identified as top priorities, and eight other competency indicators are secondary priorities that need training. The recommended training methods to address these gaps include lecture/e-lecture, case studies, role-playing, and self-directed learning.